Surgical correction of the chronic liver purulent-septic lesions - Kotenko, O. G.; Gusev, A. V.; Popov, O. O.; Grinenko, A. V.; Grigoryan, M. S.; Yuzvuk, K. O.; Zhylenko, A. I. (Сучасні медичні технологіЈі, 2019)
Purpose of the study. The purpose of the study is to improve the results of surgical treatment of patients with purulent-septic lesion of the liver substantiating the indication for resection method use. Material and methods. The work is based on a comparative analysis of the results of examination and treatment of 64 patients aged 10 to 81 years old, with chronic liver abscesses in the department of surgery and liver transplantation during the 1995–2016 periods. According to the tasks of the study patients are divided into two groups. In 30 (46,8%) patients (the study group), various types of anatomical resection of the liver with a purulent lesion were performed without its dissection during the operation; in 34 (53,2%) patients (group of comparison) they performed the disclosure, sanation, drainage of purulent cavity. The majority of patients with chronic liver abscesses treated the abscess with a puncture or drainage method under the control of ultrasound in other medical institutions of Ukraine. Results. The results of diagnosis and treatment of 64 patients for chronic liver abscesses from 1995 to 2016 are analyzed. In the study group, the patients performed anatomical resection of the liver, in the comparison group – standard surgical interventions – the disclosure and drainage of the abscess of the liver. The duration of antibiotic therapy after surgery in the comparison group is significantly higher than in the study group, respectively, 22 ± 3,4 and 5,75 ± 1,6 days; p < 0,001. Second-line antibacterial drugs after draining operations were used more often (p < 0,001) than after resection interventions, respectively, in 94,1 and 6,6% of cases. The duration of treatment of patients in the hospital after surgery in the study group was less than in the comparison group, according to 15,1 ± 0,7 and 27,3 ± 3,05 days; total 25,9 ± 1,4 and 45,7 ± 3,45 days (p < 0,001). After drainage operations, drainages from the abdominal cavity were removed later than after resection interventions, respectively, 17,1 ± 2,8 and 6,35 ± 1,1 days (p < 0,001), through. Conclusion. Resection for chronic purulentseptic lesions of the liver is the priority methods of surgical treatment. The analysis of the obtained results allows us to conclude that resection technologies contribute to the rapid normalization of physical and social rehabilitation of patients with septic liver damage.